2023
DOI: 10.1038/s41467-023-38258-2
|View full text |Cite
|
Sign up to set email alerts
|

3D-patterned inverse-designed mid-infrared metaoptics

Abstract: Modern imaging systems can be enhanced in efficiency, compactness, and application through the introduction of multilayer nanopatterned structures for manipulation of light based on its fundamental properties. High transmission multispectral imaging is elusive due to the commonplace use of filter arrays which discard most of the incident light. Further, given the challenges of miniaturizing optical systems, most cameras do not leverage the wealth of information in polarization and spatial degrees of freedom. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 55 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…For instance, a broader selection of available printing materials offers diverse Abbe number options, facilitating the design of broadband optical devices. Beyond the wellexplored visible band, TPL can achieve precise wavefront control in the x-ray [213][214][215] band and larger wavelength bands, such as NIR and mid-infrared bands [212]. A promising candidate is a hybrid organically modified silicate-based photoresist called SZ2080™, known for its high transparency, low absorption in the UV, visible, and infrared spectra [216], and a high laser-induced damage threshold for the fabrication process [217].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a broader selection of available printing materials offers diverse Abbe number options, facilitating the design of broadband optical devices. Beyond the wellexplored visible band, TPL can achieve precise wavefront control in the x-ray [213][214][215] band and larger wavelength bands, such as NIR and mid-infrared bands [212]. A promising candidate is a hybrid organically modified silicate-based photoresist called SZ2080™, known for its high transparency, low absorption in the UV, visible, and infrared spectra [216], and a high laser-induced damage threshold for the fabrication process [217].…”
Section: Discussionmentioning
confidence: 99%
“…Drawing inspiration from color routing concepts, Roberts et al embarked on the inverse design of 3D patterned midinfrared metadevices. Employing optimization algorithms, they achieved the experimental validation of devices fabricated via TPL, showcasing the capabilities of multispectral and linear polarization sorting, OAM sorting, and Stokes polarimetry (depicted in figure 17(k)) [212]. The incorporation of intricate, multilayered nanophotonic structures marks a pivotal advancement in enhancing imaging system performance and multifunctionality.…”
Section: Other Imaging Elementsmentioning
confidence: 99%
“…These systems have similar design flexibility as multilayer meta-optics but can potentially achieve that functionality in a more compact footprint. For instance, it has been demonstrated that 3D meta-optics can achieve high efficiency spectral and polarization sorting using one, continuously structured, optical component . This functionality is not possible in single layer metasurfaces that are invariant along the optical axis without introducing reflection loss.…”
Section: Multilayer and Multielement Meta-opticsmentioning
confidence: 99%
“…Dielectric metasurfaces, which consist of subwavelength-spaced nanostructures with micron-scale thickness, have the potential to serve as ultralight and thin transmissive optics if they can be fabricated at scale over large areas. Although many early demonstrations of metasurfaces and binary subwavelength diffractive optics utilized electron-beam (e-beam) lithography or other serial point-by-point fabrication techniques, such as two-photon optical lithography, which led to skepticism about their practical scalability, metasurfaces are now produced at larger scales using modern semiconductor foundry photolithography and nanoimprinting techniques, alleviating such scaling concerns.…”
mentioning
confidence: 99%